2021
DOI: 10.3390/antiox10030488
|View full text |Cite
|
Sign up to set email alerts
|

To Synthesize Hydroxyapatite by Modified Low Temperature Method Loaded with Bletilla striata Polysaccharide as Antioxidant for the Prevention of Sarcopenia by Intramuscular Administration

Abstract: Oxidative stress has been suggested as an important factor in the progress of sarcopenia. The current treatments for sarcopenia have the disadvantages of insufficient effect or daily administration. Therefore, an alternative for effective, safety and long-term treatment may be a solution for unmet needs. Bletilla striata polysaccharide has been reported to have anti­oxidative and anti-inflammatory properties. In this study, we used Bletilla striata polysaccharide (BSP) combined with hydroxyapatite, a carrier. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…It has high ornamental value ( Xi et al, 2020 ), and its tubers are used in traditional Chinese medicine to treat gastric ulcers, inflammation, silicosis tuberculosis and pneumogastric hemorrhage ( Zhang et al, 2021 ; Zhou et al, 2021 ). Several studies have confirmed that the anti-inflammatory, antioxidant, antibacterial, and anti-tumor effects exhibited by B. striata ( Li et al, 2018 ; Xu et al, 2019 ; Liang et al, 2021 ) occur as a result of its secondary metabolites, especially extractum, polysaccharides phenolic compound, and militarine present in the tubers ( Jiang et al, 2013 ). Therefore, it is of great significance to improve the accumulation of secondary metabolites in plants.…”
Section: Introductionmentioning
confidence: 99%
“…It has high ornamental value ( Xi et al, 2020 ), and its tubers are used in traditional Chinese medicine to treat gastric ulcers, inflammation, silicosis tuberculosis and pneumogastric hemorrhage ( Zhang et al, 2021 ; Zhou et al, 2021 ). Several studies have confirmed that the anti-inflammatory, antioxidant, antibacterial, and anti-tumor effects exhibited by B. striata ( Li et al, 2018 ; Xu et al, 2019 ; Liang et al, 2021 ) occur as a result of its secondary metabolites, especially extractum, polysaccharides phenolic compound, and militarine present in the tubers ( Jiang et al, 2013 ). Therefore, it is of great significance to improve the accumulation of secondary metabolites in plants.…”
Section: Introductionmentioning
confidence: 99%
“…They were tested on the treadmill and their grip strength, and the antioxidant supplement employed in this study was Bletilla striata (BSP). Finally, the authors observed that BSP improved grip strength, muscular mass, and muscular endurance in these rats (Table 1) [100].…”
Section: Sarcopenia Antioxidant Supplementation and Exercisementioning
confidence: 87%
“…Regular exercise is an essential strategy to avoid sarcopenia, but many older individuals are unwilling to exercise due to sarcopenia's complicated nature, with its disease-related and age-related signs [99]. Liang et al (2021) studied male Sprague-Dawley rats. Lipopolysaccharide (LPS) muscle injury was used to produce ROS and sarcopenia.…”
Section: Sarcopenia Antioxidant Supplementation and Exercisementioning
confidence: 99%
“…Additionally, BSP fraction exhibited signi cant gastroprotective effects against ethanol-induced gastric mucosal lesion in rats by decreasing pro-in ammatory cytokines production, relieving oxidative stress and inhibiting MAPK/NF-κB pathways (Zhang et al 2019). The antioxidant effect was also con rmed that BSP could suppress lipopolysaccharide-induced ROS generation in C2C12 myoblasts (Liang et al 2021). Interestingly, some evidences showed that BSP had good anti-in ammatory and antioxidant effects to enhance endothelial cell proliferation and wound healing, suggesting its potential role in the recovery of tissue repair (Chen et al 2020a;Chen et al 2020b;Lai et al 2018).…”
Section: Introductionmentioning
confidence: 85%